Development of node-red monitoring fish pond quality system and notification system for aquaculture - See, Wan Chun
The proposed loT smart fish farming is implement to monitor the condition of water. The indoor water system is recirculating system and all the water tank are connected, so the water quality is the crucial factor to determine the quality of the fish. The DFRobot analog electrical conductivity sensor and DFRobot analog pH sensor were used to monitor the parameters of aquaculture water quality. Due to Node-RED is a visual tool from IBM that helps in building loT workflows by chaining IoT device, therefore Event Driven System will be created by Node-RED to send the alarm notification for the fish growers to take actions as fast as they can when the water parameter is out of range. This proposed work that supports remote monitoring of the fish farming framework based on the Internet of Things (lo1) with Arduino Uno board connected to the Raspberry PI and Wireless sensor network (WSN) for continuous monitoring of a fish farming. The data analysis can be made from the reading stored in Raspberry Pi and the storage space of data was determined by the size of memory card we put in Raspberry Pi. Thus, the suggested loT monitoring system implemented as a basic smart fish farming concept to the fish field as it could give the higher economical return.